Neurological Worsening in a Child of Miliary Tuberculosis with Neuro-Tuberculosis on Anti Tubercular Treatment - Arora, Sunita; Narang, Gursharan Singh; Dhillon, Prabhjot Kaur (Journal of Nepal Paediatric Society, 2016)
A seven and half year old male child presenting with pyrexia of unknown origin was diagnosed to be a case of miliary tuberculosis. Neuroimaging revealed multiple discrete ring as well as nodular enhancing lesions indicative of tuberculomas. After the initial response to ATT along with systemic steroids the child again presented with severe headache along with vomiting towards the end of intensive phase. Repeat neuroimaging showed appearance of new lesions with perilesional edema. Child was started again on systemic steroids and Streptomycin was added to the anti tubercular regimen, to which the child responded well. J Nepal Paediatr Soc 2015;35(2):185-188